Spectral analysis of pulsed electromagnetic fields in remote sensing and biomedicine - Батраков, Д. О.; Антюфеева, М. С.; Антюфеев, А. В. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
Using the ultra-wideband (UWB) pulses for the frequency dependence of the reflection coefficient of the plane-layered media and the subsequent application of the Newton-Kantorovich scheme to solving inverse scattering problems is proposed in the paper. Taking into account the specificity of the tasks, algorithms and software for amplitude analysis and phase characteristics of the pulse signals reflected from the plane-layered media are developed. Provided computing experiments for modeling reflection of UWB pulse signals from such media allowed to justify the choice of frequency range of samples of the reflection coefficients for the solution of the inverse problem. The obtained results should be applied to nondestructive testing and in biomedical research